An Efficient Method for the Synthesis of Isoxazolines Under Microwave Irradiation and Solvent-Free Conditions - O. Patil, Pravin; B. Bari, Sanjay. (Asian Journal of Chemistry, 2013)
A facile method for the synthesis of new isoxazoline derivatives are being reported starting from substituted 1-(1H-indol-3-yl)-3-(substituted aryl)-prop-1-en-3-ones and hydroxylamine hydrochloride under solvent free conditions and microwave irradiation. This approach has advantages such as short reaction time, moderate to excellent yield, over the conventional synthesis. The structures of the compounds were confirmed by 1H NMR, IR, mass spectra and elemental (C, H, N) analysis.